Infusion‐related febrile reaction after haploidentical stem cell transplantation in children is associated with higher rates of engraftment syndrome and acute graft‐versus‐host disease. (2nd September 2015) - Chen, Yao; Huang, Xiao‐Jun; Liu, Kai‐Yan; Chen, Huan; Chen, Yu‐Hong; Zhang, Xiao‐Hui; Wang, Feng‐Rong; Han, Wei; Wang, Jing‐Zhi; Wang, Yu; Yan, Chen‐Hua; Zhang, Yuan‐Yuan; et al.
Abstract: The clinical significance and prognostic impact of IRFR in pediatric recipients of haploidentical SCT are not clearly understood. Therefore, we attempted to determine how IRFR affects clinical outcomes in children. Clinical data from 100 consecutive pediatric patients (60 boys and 40 girls; median age, 12 yr [range, 2–18 yr] after haploidentical SCT between January 2010 and December 2012 were collected retrospectively. IRFR was described as unexplained fever (>38 °C) within 24 h after the infusion of haploidentical PBSCs. Thirty‐eight (38.0%) cases met the criteria for IRFR. ES was found in 24 (63.2%) of the 38 children with IRFR, with the median time of developing ES of +9 (7–16) days, while only 15 (25.4%) of the 59 children without IRFR were found with ES (p < 0.001). Similarly, the cumulative incidence rates of grade II–IV aGVHD were 50.0% in the IRFR group and 29.3% (p = 0.012) in the non‐febrile group. Multivariate analysis identified IRFR as the risk factor for ES and aGVHD. In the haploidentical setting, IRFR is associated with the development of ES and aGVHD. We attempted to determine how IRFR affects clinical outcomes in children after haploidentical SCT. Thirty‐eight children comprised the IRFR group, and 59 were in the control (non‐IRFR) group. High incidence of ES was observed in children with the occurrence of IRFR. Similarly, the incidence of stage I–IV and II–IV aGVHD was significantly higher in the febrile group. Multivariate analysis showed IRFR to be the risk factor for ES and aGVHD.